v.1 - "Wuthnow, Robert. (ed.)" (Washington D.C, 2007)
''''No other resource examines the complex interconnections between politics and religion with the depth and scope of this critically acclaimed work. Now available in a revised and updated second edition, Encyclopedia of Politics and Religion is the only reference work that addresses the intersection of these two powerful forces as it plays out in our world today. ''''The content of the second edition has been significantly revised and updated, and includes nearly 50 new articles on subjects including European Islam, Creationism and Evolution, Palestine, Radical Islam, the Christian Right, and more.''''The Encyclopedia of Politics and Religion features:''''Approximately 300 signed articles that trace the historical roots of the relations between politics and religion in the modern world and consider how these two elemental institutions of society have combined to shape public discourse, affect social attitudes, spark and sustain collective action, and influence policy, especially over the past two centuries''''Compelling essays written at the general encyclopedia level by recognized world experts representing a multitude of voices and perspectives''''Coverage of all the significant and emerging individuals, institutions, countries, regions, and events--as well as such cross-cultural themes as pluralism, cults, and the relationship of church and state'' ''Focus on the past 200 years with explorations of how politics and religion interact in various cultures around the globe''''Comprehensive reference aids, including a unique appendix of documents relating to politics and religion, a helpful glossary of important terms, and a complete index in the back of each volume'' ''Engaging maps, photographs, and illustrations'' ''Encyclopedia of Politics and Religion features a unique international scope and reliable, in-depth articles that will serve researchers in virtually any library. Scholars, students, religious leaders, policy makers, and general readers will all benefit from this important reference resource on some of the most pressing social issues of our time.''''
Keywords: Religion and politics-Encyclopedias